Influence of Air‐Drying on the Quality Characteristics of Spearmint: Effects of Air Temperature and Velocity. Issue 2 (1st July 2016) - Orphanides, Antia; Goulas, Vlasios; Botsaris, George; Gekas, Vassilis
Abstract: Dry spearmint is a commodity widely used in food manufacturing both as an ingredient and a product itself. The objective of this study was to determine the effect of different drying temperatures and air velocities on the quality of dried product in an attempt to recommend the optimum drying conditions. Physicochemical and microbiological properties were evaluated as quality indexes. Results revealed that temperature and air velocity were statistically significant for most of the parameters investigated. Taking into consideration that consumers have a preference towards dried herbs that retain the characteristics of the fresh material, the suggested combination for drying spearmint is at 40C with an air velocity of 3 m/s. This combination has been experimentally demonstrated that can also significantly improve the microbiological quality of the product. Practical Applications: Drying process is often applied to preserve and increase self‐life of leafy aromatic plants through decreasing moisture content and water activity. Through the present work the effect of air‐drying on the quality attributes of dried spearmint was investigated. Different combinations of temperature and air velocities were tested in an attempt to determine the most suitable drying parameters that will lead to a high quality product. The application proposed at 40C with an air velocity of 3 m/s can be adopted by manufactures in industrial scale. The aforementioned combination produced dried spearmint with the best physicochemical and microbiological characteristics.